1964
DOI: 10.1021/ac60215a041
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Carbon in Sodium by Isotope Dilution Mass Spectrometry.

Abstract: A method utilizing isotope dilution mass spectrometry has been developed for the determination of carbon in sodium. The details of the method are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1964
1964
2000
2000

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…A study of previous methods (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) revealed several areas where a different approach would eliminate problems. Broadly outlined, these areas are as follows: sampling and handling methods requiring minimum environmental contact; reduction of the blank to very low values by the use of carbonfree or low-carbon materials in the apparatus; a combustion method which ensures that the sodium oxide produced cannot retain carbon combustion products and that all the carbon converts to C02; and a method capable of reproducible measurements of the C02.…”
Section: Discussionmentioning
confidence: 99%
“…A study of previous methods (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) revealed several areas where a different approach would eliminate problems. Broadly outlined, these areas are as follows: sampling and handling methods requiring minimum environmental contact; reduction of the blank to very low values by the use of carbonfree or low-carbon materials in the apparatus; a combustion method which ensures that the sodium oxide produced cannot retain carbon combustion products and that all the carbon converts to C02; and a method capable of reproducible measurements of the C02.…”
Section: Discussionmentioning
confidence: 99%
“…and titrimetry a r e used and it is assumed the gas being measured is C02. These methods a r e being replaced by the specific, and generally more sensitive techniques of gas chromatography(4) and mass spectrometry, (8) which identify a s well a s measure the quantity of gases found.…”
Section: Introductionmentioning
confidence: 99%
“…A study of previous methods (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) revealed several areas where a different approach would eliminate problems. Broadly outlined, these areas are as follows: sampling and handling methods requiring minimum environmental contact; reduction of the blank to very low values by the use of carbonfree or low-carbon materials in the apparatus; a combustion method which ensures that the sodium oxide produced cannot retain carbon combustion products and that all the carbon converts to C02; and a method capable of reproducible measurements of the C02.…”
mentioning
confidence: 99%